Portable Water Sampling Kit / Wan Muhamad Norazwan Wan Abu Bakar, Mohd Azmieludin Mohd Suhaimi and Nik Muhammad Hanif Nik Man - Wan Abu Bakar, Wan Muhamad Norazwan; Mohd Suhaimi, Mohd Azmieludin; Nik Man, Nik Muhammad Hanif (2017)
Water quality unit is one of the main scopes of Environmental Health Officer in Health District Office. The main objective of water quality unit is to elevate the health of the public by ensuring that the supplied drinking water is safe and acceptable to the consumers. The main goal of this project is to create a portable water sampling unit that can run the test for all three physical parameter of water that is residue forchlorine, the temperature of water, Ph of the water and water turbidify. Environmental Health Officer (EHO) needs to carry 3larger sampling unit that tests all of this parameter nowadays.